A Reverence for Rivers: Imagining an Ethic for Running Waters. By Kurt D.Fausch, Corvallis: Oregon State University Press, 2025. 278 pp. ISBN: 978‐1‐96‐264534‐8 - Samuel Shephard (Fish and Fisheries, 2026)

Body condition of returning Atlantic salmon Salmo salar L. correlates with scale δ 13 C and δ 15 N content deposited at the last marine foraging location - Rory Feeney; Clive N. Trueman; Patrick G. Gargan; William K. Roche; Samuel Shephard (Journal of Fish Biology, 2024)
Patterns of feeding and growth of Atlantic salmon Salmo salar L. in the marine environment are critical to understanding how observed declines in recruitment may reflect warming or other oceanic drivers. The isotopic composition of scales can provide insight into differences in marine feeding location and possibly temperature regime. The authors used archived scale samples to measure δ 13 C and δ 15 N deposited in the scales of one sea‐winter (1SW) salmon during their last season of growth at sea before they returned to five Irish rivers. δ 13 C values were related statistically to observed salmon body condition (Fulton’s K), and fish with higher δ 13 C values tended to show significantly better condition. In contrast, δ 15 N values were negatively related to body condition. There was no important effect on condition of length at smolt migration, and the effect of duration of marine residence varied among rivers. It is likely that δ 13 C values partly reflected ambient ocean temperature and recent marine feeding environment before return migration, such that the observed relationship between higher δ 13 C values and increased body condition may express an advantage for adult fish feeding in warmer, potentially closer, waters. If greater body condition influences fitness, then a changing temperature regime in the Northeast Atlantic may drive shifts in salmon survival and reproduction. This study provides evidence that there is spatial and trophic variation at sea between salmon from rivers of origin that are located relatively close to each other, with potential consequences for body condition and, consequently, fitness and life history; this suggests that salmon populations from geographically proximate rivers within regions may exhibit differential responses to ocean‐scale climatic changes across the Northeast Atlantic.

New directions for Indigenous and local knowledge research and application in fisheries science: Lessons from a systematic review - Benjamin L. H. Jones; Rolando O. Santos; W. Ryan James; Sophia V. Costa; Aaron J. Adams; Ross E. Boucek; Lucy Coals; Leanne C. Cullen‐Unsworth; Samuel Shephard; Jennifer S. Rehage (Fish and Fisheries, 2024)
Social‐ecological systems like fisheries provide food, livelihoods and recreation. However, lack of data and its integration into governance hinders their conservation and management. Stakeholders possess site‐specific knowledge crucial for confronting these challenges. There is increasing recognition that Indigenous and local knowledge (ILK) is valuable, but structural differences between ILK and quantitative archetypes have stalled the assimilation of ILK into fisheries management, despite acknowledged bias and uncertainty in scientific methods. Conducting a systematic review of fisheries‐associated ILK research ( n = 397 articles), we examined how ILK is accessed, applied, distributed across space and species, and has evolved. We show that ILK has generated qualitative, semi‐quantitative and quantitative information for diverse taxa across 98 countries. Fisheries‐associated ILK research mostly targets small‐scale and artisanal fishers (70% of studies) and typically uses semi‐structured interviews (60%). We revealed large variability in sample size ( n = 4–7638), predicted by the approach employed and the data generated (i.e. qualitative studies target smaller groups). Using thematic categorisation, we show that scientists are still exploring techniques, or ‘validating’ ILK through comparisons with quantitative scientific data (20%), and recording qualitative information of what fishers understand (40%). A few researchers are applying quantitative social science methods to derive trends in abundance, catch and effort. Such approaches facilitate recognition of local insight in fisheries management but fall short of accepting ILK as a valid complementary way of knowing about fisheries systems. This synthesis reveals that development and increased opportunities are needed to bridge ILK and quantitative scientific data.

Length-based assessment of an exploited coastal pike (Esox lucius) stock (Rügen, southern Baltic Sea) underscores the crucial relevance of growth and natural mortality for assessment outcomes - Colm J. Fitzgerald; Jan S. Droll; Samuel Shephard; Christopher T. Monk; Timo Rittweg; Robert Arlinghaus (Fisheries Research, 2023)

Community‐based monitoring, assessment and management of data‐limited inland fish stocks in North Rupununi, Guyana - Samuel Shephard; Kevin Edwards; Susan George; Elvis Joseph; Samantha James; Oswin David; Addevi Persaud; L. Cynthia Watson; Nathalie Van Vliet (Fisheries Management and Ecology, 2023)
Inland fisheries are important for food security in communities around the world, especially in developing countries. In North Rupununi, Guyana, the state of exploited stocks is poorly understood, and fishery monitoring and assessment are challenging because diverse fishing gears and target species are distributed across a heterogeneous landscape. This complexity created an opportunity for community‐based monitoring (CBM) to support data‐limited assessment. Standardised CBM was established for the North Rupununi as part of a new inland fisheries management plan initiated by indigenous community groups with support from the government. Quantitative length‐based assessments undertaken for target stocks suggested moderate levels of exploitation consistent with local perception. Our study highlights that local experts and community participants with different levels of training can collect accurate biodiversity data. Further development of CBM is important in North Rupununi. We recommend using local ecological knowledge indicators to track spatial and temporal patterns in exploitation and fish stock status.

Reviving the unique potential of recreational fishers as environmental stewards of aquatic ecosystems - Samuel Shephard; Charles J. List; Robert Arlinghaus (Fish and Fisheries, 2023)
Recreational anglers have been key players in aquatic conservation, but this role is increasingly obscured. Other environmental sectors are now more visible stakeholders engaged with biodiversity. Recreational fishing has relevant environmental and moral implications, but these can be resolved via improved governance and management. More difficult is replacing the stewardship capacity provided by anglers. When analysed against a novel environmental stewardship framework based on place and identity, care, knowledge and agency, we find that marginalizing anglers could diminish aquatic biodiversity conservation. This outcome is likely because excellence in recreational fishing involves habituation of skills and ethical imperatives associated with sustainable and responsible use of fish populations. These dimensions are probably not so pertinent and correspondingly less developed in other nature stakeholders. Importantly, catching and killing wild animals catapults anglers into a food web and associated ecological conscience that most other outdoor activities cannot generate. As a result, recreational fishing often engenders feelings of care and responsibility for aquatic systems that support personal well‐being, bridging the stewardship value‐action gap through development of local assessment, management and evaluative competencies and associated agency. Transdisciplinary cooperation with scientists, managers and policymakers can unleash the stewardship potential of recreational anglers and engage their capacity for the common good.

The spawning location of vulnerable ferox trout ( Salmo trutta L. ) in the Lough Corrib and Lough Mask catchments, Western Ireland - Patrick G. Gargan; Finn Økland; Samuel Shephard; Colm Fitzgerald; Martin O'Grady (Journal of Fish Biology, 2021)
Ferox trout are large, long‐lived, piscivorous trout normally found in deep lakes; they are highly prized by trophy anglers. Lough Corrib and Lough Mask, Western Ireland, have recorded the majority of Irish specimen ferox trout since angling records began. Little was known regarding the spawning location of ferox trout relative to sympatric brown trout, and a radio telemetry study was initiated in both catchments in 2005. Over the period 2005–2009, 79 ferox were captured by angling and radio tagged in Lough Corrib, while 55 ferox were tagged in Lough Mask. Manual and helicopter tracking were carried out on all spawning streams entering both lakes over the autumn/winter period to detect tagged fish. Overall, 37 radio‐tagged trout (46.8%) were detected in Lough Corrib streams and 21 tagged trout (38.2%) were recorded from Lough Mask streams. Results from radio tracking indicate that the majority (92%) of ferox trout tagged in Lough Corrib spawned in a single spawning stream, the Cong river, while the majority (76%) of ferox trout tagged in Lough Mask spawned in the Cong canal and Cong river. These results suggest that these streams are most likely the principle spawning locations of ferox trout in both lakes. The occurrence of ferox trout predominantly in single spawning rivers in both catchments highlights the vulnerability of the study ferox populations. As a result of these findings, conservation measures were introduced for ferox trout in both catchments.

Informing CITES Parties: Strengthening science‐based decision‐making when listing marine species - Kim Friedman; Matias Braccini; Matthew Bjerregaard‐Walsh; Ramón Bonfil; Corey J. A. Bradshaw; Stephen Brouwer; Ian Campbell; Rui Coelho; Enric Cortés; Wetjens Dimmlich; Michael G. Frisk; Irene Kingma; et al. (Fish and Fisheries, 2020)
International trade in vulnerable marine species is regulated once they are listed in CITES Appendices (the Convention on International Trade in Endangered Species of Wild Fauna and Flora). Parties to the Convention submit proposal(s) 150 days prior to the CITES Conference for voting on the inclusion of new species in Appendices I and II, making a case for why CITES listing criteria are met in each case. Before the vote, Parties receive advice from (a) the Food and Agriculture Organization of the United Nations, (b) the International Union for Conservation of Nature—TRAFFIC and (c) the CITES Secretariat, among others. This paper offers an expert review of listing processes, which are the subject of much debate in fishery and environment‐protection communities, looking at two specific cases: silky shark ( Carcharhinus falciformis, Carcharhinidae) and bigeye thresher shark ( Alopias superciliosus, Alopiidae). The reviewers determine that the evidence made available to voting Parties is substantial, but suffers from non‐standard presentation across assessments. The best available data are not always presented or described transparently in relation to CITES criteria. An extension of the assessment period, as well as the opportunity to refute evidence, has been suggested as ways to support more informed and effective decision‐making by CITES Parties, whose composition of delegations varies greatly in their experience of marine species management and trade. Experts welcomed a greater coherence of advice between fishery and non‐fishery sources in the long term, and proposed a range of suggested improvements for the delivery of information and advice to CITES Parties.

Potential climate change impacts on Arctic char Salvelinus alpinus L. in Ireland - Lynda Connor; Samuel Shephard; Kieran Rocks; Fiona L. Kelly (Fisheries Management and Ecology, 2019)
Climate change has been identified as a global threat to Arctic char Salvelinus alpinus L. populations. Bayesian statistical models were used to identify important physical and ecological factors explaining Arctic char presence and persistence in Irish lakes. Maximum lake depth and the presence of mixed fish communities (i.e. including non‐salmonid fish species) were the most important drivers of Arctic char presence. There was a 75% probability that an Irish lake would contain Arctic char when maximum depth exceeded 40 m, if only a salmonid community was present. However, the required depth increased to 57 m when a mixed fish community (e.g. pike, perch or roach) was present. Similar variables explained char persistence, with surviving Arctic char populations being more likely in lakes with greater maximum depth and fewer non‐salmonid fish species. Tested temperature covariates were not important in explaining Arctic char presence or persistence in Irish lakes. A risk analysis was undertaken to identify which Arctic char lakes are vulnerable to colonisation by thermally plastic mixed fish communities due to flooding. Results indicated that 32 out of 45 lakes were not at any risk from the colonisation of thermally plastic mixed fish communities and 13 lakes had some level of risk.

River modification reduces climate resilience of brown trout ( Salmo trutta ) populations in Ireland - Rossa O'Briain; Brian Coghlan; Samuel Shephard; Fiona L. Kelly (Fisheries Management and Ecology, 2019)
This study investigated interactions between eco‐hydromorphological state, riparian vegetation cover, water temperature and fish community composition in lowland rivers in Ireland. Physical habitat modification of study sites corresponded with degraded eco‐hydromorphological state (degree of ecological and physical modification) and reduced thermal buffering capacity (greater temperature fluctuation and increased frequency of extreme temperature events). This impact was reflected in the fish community, with a shift from a brown trout‐dominated ( Salmo trutta L.) fish assemblage to predominance of the more thermally plastic minnow, Phoxinus phoxinus (L.), and stone loach, Barbatula barbatula (L.). Eco‐hydromorphological state may be a central factor affecting the ability of temperate rivers to resist temperature change in a warming climate and to maintain suitable conditions for salmonids and other cold‐water biota. Strategies aimed at climate change proofing of temperate rivers should focus on preserving or re‐establishing the eco‐hydromorphological processes that create habitat complexity and buffer stream temperature.

Shifts in diet of an apex predator following the colonisation of an invasive fish - Paul McLoone; Samuel Shephard; Sinead O’Reilly; Fiona Kelly (Hydrobiologia, 2019)

Non‐native species and lake warming negatively affect Arctic char Salvelinus alpinus abundance; deep thermal refugia facilitate co‐existence - Emma Morrissey‐McCaffrey; Samuel Shephard; Fiona L. Kelly; Mary Kelly‐Quinn (Journal of Fish Biology, 2019)
This study finds that non‐native species and warming temperatures have significant negative effects on Arctic char Salvelinus alpinus abundance in Irish lakes. Eutrophication was not important at the range of total phosphorus tested (0.005–0.023 mg l −1 ). Model results predict that S. alpinus occur across the temperature range sampled (8.2–19.7°C) when non‐natives are absent, but S. alpinus catch is predicted to be close to zero irrespective of temperature when non‐native catch is high. This result indicates that to persist, S. alpinus may require a habitat where non‐natives are at low abundance or absent. Salvelinus alpinus segregated from other species along the thermal axis, inhabiting significantly colder water and actively avoided non‐native species, which appeared to limit their distribution. The thermal niche realized by S. alpinus in non‐native dominated lakes was thus compressed relative to native dominated lakes and S. alpinus population density was significantly lower. These findings were consistent even when the only non‐native present was Perca fluviatilis . Temperature appeared to limit the distribution of non‐native species, such that the presence of deep thermal refugia is currently facilitating S. alpinus co‐existence with non‐natives in associated lakes. Diet analysis identified P. fluviatilis as potential predators and competitors. This study provides strong evidence that non‐native species are a key driver of low S. alpinus abundance in Irish lakes. Temperature increases associated with climate change are identified as a secondary concern, as they could erode S. alpinus ' thermal niche and lead to their extirpation. The lower thermal buffering capacity of shallow lakes identifies these as higher risk systems. Salvelinus alpinus conservation in Ireland should focus on preventing future illegal non‐native species introductions because unlike other stressors ( e.g ., eutrophication etc.), species introductions are rarely reversible.

Coexistence of pike Esox lucius and brown trout Salmo trutta in Irish lakes - Paul McLoone; Samuel Shephard; Karen Delanty; Kieran Rocks; Rory Feeney; Fiona Kelly (Journal of Fish Biology, 2018)
An environmental study of pike Esox lucius recorded their presence in 522 Irish lakes and that they coexisted with brown trout Salmo trutta in 97 of these. Statistical models, accounting for spatial non‐independence among lakes, suggested that lakes with greater area, maximum depth and stream connectivity show a higher probability of coexistence. Introductions of E. lucius are likely to have negative effects on S. trutta stocks in small isolated lakes, but coexistence may be possible in larger systems.

Inland fish stock assessment: Applying data‐poor methods from marine systems - Colm J. Fitzgerald; Karen Delanty; Samuel Shephard (Fisheries Management and Ecology, 2018)
Inland fisheries can be diverse, local and highly seasonal. This complexity creates challenges for monitoring, and consequently, many inland fish stocks have few data and cannot be assessed using methods typically applied to industrial marine fisheries. In such situations, there may be a role for methods recently developed for assessment of data‐poor fish stocks. Herein, three established data‐poor assessment tools from marine systems are demonstrated to highlight their value to inland fisheries management. A case study application uses archived length, catch and catch‐per‐unit‐effort data to characterise the ecological status of an important recreational brown trout stock in an Irish lake. This case study is of specific use to management of freshwater sport fisheries, but the broader purpose of the paper was to provide a crossover between marine and inland fisheries science, and to highlight accessible data‐poor assessment approaches that may be applicable in diverse inland systems.

Fishing impact and environmental status in E uropean seas: a diagnosis from stock assessments and ecosystem indicators - Didier Gascuel; Marta Coll; Clive Fox; Sylvie Guénette; Jérome Guitton; Andrew Kenny; Leyla Knittweis; J Rasmus Nielsen; Gerjan Piet; Tiit Raid; Morgane Travers‐Trolet; Samuel Shephard (Fish and Fisheries, 2016)
Stock‐based and ecosystem‐based indicators are used to provide a new diagnosis of the fishing impact and environmental status of E uropean seas. In the seven European marine ecosystems covering the B altic and the N orth‐east A tlantic, (i) trends in landings since 1950 were examined; (ii) syntheses of the status and trends in fish stocks were consolidated at the ecosystem level; and (iii) trends in ecosystem indicators based on landings and surveys were analysed. We show that yields began to decrease everywhere (except in the B altic) from the mid‐1970s, as a result of the over‐exploitation of some major stocks. Fishermen adapted by increasing fishing effort and exploiting a wider part of the ecosystems. This was insufficient to compensate for the decrease in abundance of many stocks, and total landings have halved over the last 30 years. The highest fishing impact took place in the late 1990s, with a clear decrease in stock‐based and ecosystem indicators. In particular, trophic‐based indicators exhibited a continuous decreasing trend in almost all ecosystems. Over the past decade, a decrease in fishing pressure has been observed, the mean fishing mortality rate of assessed stocks being almost halved in all the considered ecosystems, but no clear recovery in the biomass and ecosystem indicators is yet apparent. In addition, the mean recruitment index was shown to decrease by around 50% in all ecosystems (except the B altic). We conclude that building this kind of diagnosis is a key step on the path to implementing an ecosystem approach to fisheries management.

Footprints in the sand: a persistent spatial impression of fishing in a mobile groundfish assemblage - Francisco de Castro; Samuel Shephard; Sarah B. M. Kraak; David G. Reid; Keith D. Farnsworth (Marine Biology, 2015)

Can bottom trawling indirectly diminish carrying capacity in a marine ecosystem? - Samuel Shephard; Deirdre Brophy; David G. Reid (Marine Biology, 2010)

Strengthening recruitment of exploited scallops Pecten maximus with ocean warming - Samuel Shephard; Bryce Beukers-Stewart; Jan G. Hiddink; Andrew R. Brand; Michel J. Kaiser (Marine Biology, 2010)